2021
DOI: 10.1109/access.2021.3051526
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Subjective Argument Quality Aspects From Social Signals in Argumentative Dialogue Systems

Abstract: Information about a subjective user opinion towards an argument is crucial for argumentative systems in order to present appropriate content and adapt their behaviour to the individual user. However, requesting explicit feedback regarding the discussed arguments is often impractical and can hinder the interaction. To address this issue, we investigate the automatic recognition of user opinions towards arguments that are presented by means of a virtual avatar from social signals. We focus on two different user … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…They all rank arguments by relevance to the user-specified topic, while some of them present extra information for each argument such as supporting evidence, its stance score (denoting the extent to which it supports or refutes the claim) or its relevance score. While these are closer to the kinds of applications we envision for the Web of Debates, their performance is still limited as, for example, evidenced by the results of a recent user-based evaluation, which showed that they do not significantly outperform conventional search engines especially with respect to the convincingness of the arguments they retrieve (Rach et al, 2020). This can be attributed on the one hand to the limitations of the argument mining methods they use, and on the other to the lack of a method to assess the quality or persuasiveness of arguments.…”
Section: Motivating Examplementioning
confidence: 99%
“…They all rank arguments by relevance to the user-specified topic, while some of them present extra information for each argument such as supporting evidence, its stance score (denoting the extent to which it supports or refutes the claim) or its relevance score. While these are closer to the kinds of applications we envision for the Web of Debates, their performance is still limited as, for example, evidenced by the results of a recent user-based evaluation, which showed that they do not significantly outperform conventional search engines especially with respect to the convincingness of the arguments they retrieve (Rach et al, 2020). This can be attributed on the one hand to the limitations of the argument mining methods they use, and on the other to the lack of a method to assess the quality or persuasiveness of arguments.…”
Section: Motivating Examplementioning
confidence: 99%
“…Dialogue Systems In the realm of visualization, a novel approach gaining attraction is the integration of dialogue systems to enhance the interaction between users and visual representations. Dialogue systems, commonly known as chatbots like ChatGPT, have been increasingly explored for their potential to facilitate information comprehension (Rach et al, 2020;Wambsganß et al, 2021).…”
Section: Visualization -How To Show the Error?mentioning
confidence: 99%
“…Systems introduced so far include the one developed in the scope of IBM project debater , Argu-menText (Stab et al, 2018), args.me (Wachsmuth et al, 2017b), TARGER (Chernodub et al, 2019) and PerspectroScope . The general applicability of argument search engines in the context of dialogue systems was assessed in (Rach et al, 2020a) where ArgumenText and args.me were compared to a baseline system. Although a mapping into argument structures was not addressed, we use the discussed results to select a suitable search engine for the present work.…”
Section: General Approachmentioning
confidence: 99%